View of the Garbhagriha of Santoshi Mata Temple - Mumbai Archive Project Team (Jio Institute, 2024)
The blockbuster hit movie Jai Santoshi Maa legitimized Santoshi Maa as a mother goddess in the Koli pantheon with iconography borrowed from other mother goddesses. For example, her characteristic posture while sitting on a lotus mirrors that of the goddess Shri Lakshmi. The weapons she holds—the sword and the trident—are traditional attributes of the goddess Devi Durga.